The Influence of Viral Marketing and Celebrity Endorser on Purchase Decisions on Scarlett Whitening Products: Case study on Widyatama Female Students - Sukma, Andhi; Deviana, Zavira Bulan (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The purpose of this study is to examine and identify the ways in which viral marketing and celebrity endorsement of Scarlett Whitening products affect consumer choice. The writers hope to be able to provide readers with new knowledge and advice about how to select goods that will spark their interest for purchase, especially those that are related to the issue under investigation. 150 female Widyatama respondents were used as a sample in this study. The sample approach used in this study is non-probability sampling. The type of non-probability sampling process chosen is called purpose sampling, which has significant considerations. The study's data came from primary sources. Data was gathered through distributing questionnaires. The descriptive and assessed quantitative methods of this study